DEVELOPMENT TRENDS OF UNMANNED ROBOTIC SYSTEMS: EXPERIENCE OF DOMESTIC AND FOREIGN MANUFACTURERS - M. N. Artemenko; P. A. Korchagin; I. A. Teterina (Вестник СибАДИ, 2019)
Introduction. Nowadays robotics is one of the most important directions of fundamental, technical, scientific and applied research. The main robotics’ challenges are to develop schemes for obtaining information about environment and the creation of artificial intelligence effective systems of the complex dynamic objects’ control in uncertainty conditions. Recently, robotics is going through the stage of rapid development, more and more covering the civilian and military spheres of human activity. The number of developed and implemented mobile unmanned robotic complexes of military and dual-use exceeds the number of robotic complexes in progress. The purpose of the research is to review the most promising samples of mobile unmanned robotic equipment used in various fields of human activity.Results. The paper reviewed the modern developments of mobile unmanned robotic complexes applied in the agricultural complex, industrial and civil construction, and in cargo transportation. The authors analyzed promising samples of Russian and foreign unmanned robotic technology. Moreover, the authors presented factors that increasingly depended on key spheres of human activities in the development and implementation of mobile robotic systems. Therefore, the paper demonstrated the list of major programs and concepts for the development of the Russian Federation in robotic sphere.Discussion and conclusions. As a result, the authors identify the basic elements of automated control systems, of navigation and autopilot system basing on mobile unmanned robotic complexes. The paper also reveals the concept of the foveal vision, which allows quickly and accurately detect pavement roughness and obstacles on the vehicle’s way.